Plan de movilidad sostenible, eficiente e incluyente para el centro de la ciudad de Neiva, como eje articulador de cultura y sociedad (2022)
The accelerated growth of the city of Neiva, lacking planning, has caused an imbalance in the different systems that make up the city, in cluding mobility, which has lagged behind and isolated from the new world trends that bet on multimodal systems. Highlighting the pedestrian and public transport as articulating engines of efficient and friendly mobility. Taking into account the new world trends and the existing road infrastructure, a sustainable, efficient and inclusive mobility plan for the city center is proposed, which aims to balance the loads in the different systems and promote equity between vehicles. and the pedestrians. It mainly seeks to update the road infrastructure, in order to reduce travel times, expand public space and integrate it efficiently with the road network. Keywords: sustainable, city . Multimodal, mobility, infrastructure, road, public space, pedestrian, vehicle,